Conversations with Technology Leaders: Erik Meijer. - MATSUDAIRA, KATE (Communications of the ACM, 2017)
An interview with software programming Erik Meijer is presented. He discusses the skills and characteristics needed for effective software programmers and engineering managers. He recommends the book "How to Win Friends and Influence People." His beliefs about team processes and software development are described. He addresses the influence of Microsoft Corp. manager William Adams on his own management style.